"No pain, no gain": Simulation-based learning in teacher education: The mediating role of simulation hindrances - Orna Levin; Rivi Frei-Landau; Chen Goldberg (PLoS ONE, 2025)
Research on educational simulations has attempted to decipher the simulation-based learning (SBL) process by examining factors that facilitate and impede this process. In the current study, we examined the role of SBL participants’ hindrances, in particular their experience of anxiety or fear, which we view using the framework of leaving one’s comfort zone. Departure from one’s comfort zone has never been studied in the context of SBL in teacher education. A quantitative analysis of data collected via a questionnaire on Simulation Learning Outcomes in Teacher Education (SLOTE) revealed a model in which the hindrance variable potentially mediated all of the relationships between the background variables and the simulation learning outcomes (i.e., communication skills and collaborative learning insights). These results improve the theoretical understanding of the SBL process in this field and indicate ways to optimally utilize potential hindrances to plan and apply SBL for the purpose of learning.